Overinvestment, corporate governance, and dividend initiations - Officer, Micah S. (Journal of Corporate Finance, 2011)
Firms with low Tobin's Q and high cash flow have significantly more positive dividend initiation announcement returns than do other firms. I interpret this result as consistent with the hypothesis that reductions in the agency costs of overinvestment at firms with poor investment opportunities and ample cash flow are reflected in higher dividend initiation announcement returns. Further tests, such as examining the impact of governance metrics on initiation announcement returns following the dividend tax cut of 2003 and examining the long-run cash-retention policies of dividend-initiating firms, are consistent with this interpretation. There is also some evidence that is consistent with the cash flow signaling hypothesis, as dividend-initiating firms with low Tobin's Q and low pre-initiation cash flow experience substantial revisions in analysts' earnings forecasts and significantly positive initiation announcement returns.